Change in body weight and treatment outcome in sputum positive pulmonary tuberculosis patients treated under directly observed treatment short-course - Parande, Malangori A.; Borle, Pradip S.; Tapare, Vinay S.; More, Sudhakar W.; Bhattacharya, Susmita S. (International Journal Of Community Medicine And Public Health, 2018)
Background: Patients with tuberculosis often suffer from severe weight loss and is used as useful marker to predict TB treatment outcome. Hence a study was planned with an objective to determine the change of patient’s body weight over time throughout treatment and to determine whether there was any association with treatment outcome. Methods: This was a retrospective cohort study, planned to be conducted among all smear positive pulmonary tuberculosis patients registered in a Tuberculosis Unit of Pune corporation, during the period of January to December 2015. Body weights of patients were recorded from TB treatment cards at the time of diagnosis, after 2 months of intensive phase of treatment and at the end of treatment. Total 344 cases were enrolled. Chi-Square test and Fisher’s exact test and repeated measure ANOVA test was used for analysis. Results: A bad outcome was more likely among the category II cases as compared to category I, among non-adherent to treatment cases in continuation phase and higher sputum grading at the time of diagnosis i. e. in 3+ sputum smear grading. The weights of the patients at the time of diagnosis, at end of intensive phase and at end of treatment showed statistical significant difference (p<0.0001). The weight gain, more so at end of treatment was significantly associated with good outcome. Conclusions: Weight gain has prognostic significance in patients with tuberculosis and should be considered as a surrogate marker to monitor response to TB treatment especially in developing countries where extensive laboratory tests are not feasible.